2021
DOI: 10.3390/molecules26164948
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Metal–Organic Framework-Derived Nanostructures in the Removal of Volatile Organic Compounds

Abstract: Air is the most crucial and life-supporting input from nature to the living beings of the planet. The composition and quality of air significantly affects human health, either directly or indirectly. The presence of some industrially released gases, small particles of anthropogenic origin, and the deviation from the normal composition of air from the natural condition causes air pollution. Volatile organic compounds (VOCs) are common contaminants found as indoor as well as outdoor pollutants. Such pollutants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 106 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…MOFs are typically three-dimensional coordination networks with potential voids from the combination of metal clusters (secondary building units, SBUs) and organic ligands (called linkers) [ 14 ]. MOFs have already been investigated for the adsorption of VOCs such as n -hexane, xylene, toluene, acetaldehyde in vapor [ 7 , 15 ], liquid phase [ 16 , 17 ], or under humid conditions [ 18 ]. MOFs offer advantages [ 19 ] for VOC removal over materials [ 20 ] like zeolites [ 21 ], activated carbon [ 22 ], or silica gel [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are typically three-dimensional coordination networks with potential voids from the combination of metal clusters (secondary building units, SBUs) and organic ligands (called linkers) [ 14 ]. MOFs have already been investigated for the adsorption of VOCs such as n -hexane, xylene, toluene, acetaldehyde in vapor [ 7 , 15 ], liquid phase [ 16 , 17 ], or under humid conditions [ 18 ]. MOFs offer advantages [ 19 ] for VOC removal over materials [ 20 ] like zeolites [ 21 ], activated carbon [ 22 ], or silica gel [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Among these, MOFs have demonstrated great application potential in sample pretreatment because of their inherent advantages, such as structural diversity, large surface areas, more ordered pore structure, and facile synthesis. [35][36][37][38] In recent years, the direct carbonization of MOFs under inert conditions to prepare nanoporous carbon materials has gained increasing interest. Compared with other carbon materials, nanoporous carbon has excellent characteristics such as outstanding surface area, ultrahigh porosity, and ease of functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In the continuous quest of valuable solutions for air quality, metal–organic frameworks (MOFs) are recognized as an emerging class of adsorbents toward the abatement of VOCs including CCs owing to their large surface area and chemical functionality. Specific adsorption sites can be introduced in the MOF backbone either on their inorganic nodes (Lewis acid groups) or through the introduction of functional groups (−CF 3 , −alkyl chain, or – NH 2 ) on the organic linker. Their chemical diversity, tunable hydrophobicity/hydrophilicity balance, and selective sorption properties are thus exploited to optimize the host/guest interactions involved in numerous applications including gas storage, gas/liquid separation, sensing, energy conversion/storage, and catalysis. ,, MOFs have also been considered for the capture and catalytic degradation of toxic industrial chemicals, chemical warfare agents, and also environmental VOCs, even at trace levels in ambient conditions. However, until now, only a few studies have been reported on MOFs for CCs capture under humid conditions. Notably, most of the previously reported works have studied the efficiency of MOFs for the removal of only a single CC (most prominently formaldehyde) while CCs are present in the indoor environment as a gaseous mixture in which water is the most abundant interfering species.…”
Section: Introductionmentioning
confidence: 99%